اصول تعليم مهارات اللغة العربية من منظور نظرية فيجو تسكي البنائية الاجتماعية - Prabowo Adi Widayat (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Learning of Arabic language proficiency is a form of language learning with an emphasis on strengthening communication within the dimensions of the interaction language. Therefore, the concept and implementation of learning of Arabic language proficiency continues to consider aspects of the development of students in a variety of levels, for it required a theoretical idea-based language proficiency learning that includes proficiency listening, speaking, reading, and writing. Social Constructivism is a learning theory proposed by Lev Vygotsky that seeks to emphasize the importance of social interaction and cooperative learning in building depictions on the emergence of cognitive and emotional reality. In theory, the Zone Proximal Development (ZPD) patterns developed as